Design Of MultiBand Fractal Triangle Antenna For Wireless Communication Application in L Band and C Band - السموءل صالح; ولاء دليله (Latakia University Journal -Engineering Sciences Series, 2023)
The development of wireless communication systems and their entry into most disciplines has led to the development or innovation of new types of antennas used. New shapes and designs have been invented aiming to reduce losses and improve the performance and increasing efficiency of the wireless communication system because antennas are an essential component of any wireless communication system. Fractals antennas are currently considered one of the most important broadband antennas, due to the design parameters that the fractal geometry adds to these antennas. The infinite length between two specific points of the fractal antenna and its self similarity provide multi-resonant, broadband antennas ,Wideband that can operate on several applications simultaneously. This paper presents a new design for a triangular multi-frequency fractal antenna operating at (1.44,5.869 ,6.31)GHz. In the first stage we design a reference antenna operating at the frequency of 4GHz with a good value for return loss and VSWR. Then we take advantage of the Fractal geometry properties for improving the efficiency of the proposed antenna. WE obtain a fractal antenna operating at a frequency of (1.44,5.869 ,6.31)GHz with a good value for return loss and VSWR The proposed antenna was designed and analyzed using the CST simulator.